Food Waste in Primary Production: Milk Loss With Mitigation Potentials - March, Margaret D.; Toma, Luiza; Thompson, Bethan; Haskell, Marie J. (Frontiers in Nutrition, 2019)
Sources and quantities of milk loss in primary production are presented in this paper through an analysis of results from a 2018 survey. Responses from 43 dairy farms in Scotland showed that milk losses occurred due to withdrawal periods for veterinary treatment, parlour infrastructure, and lapses in management routine. A partial life cycle assessment detailed flows of milk from cow to farm gate and captured farm inputs such as imported feeds and fertilisers. Incidence of animal health events such as mastitis, that routinely lead to milk withdrawal were quantified alongside strategies carried out by farmers to reduce milk loss. Treatment for mastitis accounted for 76% of all milk withdrawal days and the remaining 24% stemmed from therapies for health events such as uterine disorders and lameness. Withdrawal periods for mastitis treatments averaged 4.5 days, with a mean incidence of 20% of cows in a herd. Across all farms, an average of 98.2% of total milk produced was sold, 0.66% was purposely retained, 0.55% was rejected due to antibiotic residues, 0.5% was lost from parlour to bulk tank infrastructure and a further 0.09% was rejected by the processor. Carbon footprints found greenhouse gas (GHG) emissions averaged 0.849kg CO2e / kg across farms for the milking herd. A scenario of 20% fewer withdrawal days reduced GHG’s on average by 0.6%. Additional mitigation was attained by reductions in milk loss from parlour infrastructure and the bulk tank, and this showed a 3.1% reduction in GHG emissions could be achieved through higher volumes of milk sales. Categorising responses by management system type highlighted differences in proportional losses between all year round housed and conventional grazing regimes. The most predominant health disorder leading to milk withdrawal was mastitis, however losses due to other health events and parlour infrastructure were not insignificant on Scottish dairy farms.